FEATURES OF THE SPREAD AND THERAPY OF PRIMARY HEADACHE SYNDROME - Mamasoliev Sh.M. (Ethiopian International Journal of Multidisciplinary Research, 2025)
A headache is an unpleasant or painful sensation of varying intensity that affects the entire head or part of it. The most common manifestations of headaches include tension headaches, migraines, and cluster pain.